OPTIMASI DAYA LASER CO2INTRAKAVITAS SEBAGAI SUMBER RADIASI SPEKTROMETER FOTOAKUSTIK DAN APLIKASINYA DALAM MENDETEKSI GAS ASETON SEBAGAI PENANDA BIOLOGISPENYAKIT DIABETES MELITUS MELALUI HEMBUSAN NAFAS MANUSIA - , MIRTHA YUNITHA SARI RISAKOTTA; , Dr. Mitrayana, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Optimation of CO2laser power intracavity as a radiation source of photoacoustic spectrometer has been done in the detection ofacetone gas for a biomarker of diabetes mellitus through human breath.This is indicated by the laser power stability in 4,5 W and the detection limits as low as (2,3 Â± 0,2) ppb. Its application to detect and measure concentration of acetone gas (C3H6O) through human breath goes well. The acetone gas concentration for volunteer patients with diabetes mellitus ranging from 129 ppb to 3872 ppb with average concentration 1685 ppb, while the acetone gas concentration for healthy volunteer ranging from 13 ppb to 139 ppb with average concentration 53 ppb.Then conducted test of two populations random using the statistical analysis of the t-test with significance value0,05 and confidence interval 95%.Quantitatively, the results of t-test showed a highly significant difference between the average acetone gas concentration for volunteer patients with diabetes mellitus and healthy volunteer.